Proposition of a Lean health-care maturity assessment instrument: a case study in the Brazilian context - Karen Thaís Alves; Cristine Hermann Nodari; Fabiano de Lima Nunes (International Journal of Lean Six Sigma, 2026)
Purpose This study aims to propose and test a specific instrument for assessing lean health-care maturity in hospitals, with the objective of supporting organizational diagnostics and fostering continuous improvement based on lean principles. Design/methodology/approach The research adopts a design science research (DSR) approach, involving the construction and validation of an artefact. The proposed instrument is grounded in the five Lean principles adapted to health care: specify value, map the value stream, establish continuous flow, implement pull systems and pursue perfection. After expert validation, the model was applied in a medium-sized hospital in southern Brazil through a case study. Findings The hospital where the case study was conducted has 69 beds and performs an average of 5.757 examinations and 490 surgeries per month. It demonstrated an intermediate level of maturity, with stronger performance in “specifying value” (Level 3) and greater challenges in “pull system” (Level 2). The instrument identified low interdepartmental integration, limited standardization and an incipient Lean culture. Despite progress in satisfaction surveys and visual management, gaps remain in heijunka, systematic audits and organizational learning. A roadmap was proposed to guide the institution’s Lean evolution. Originality/value The proposed model contributes primarily by integrating critical dimensions of hospital management, such as patient safety, strategic alignment and the use of technologies, given that the instruments identified in the literature are predominantly perception-based. It demonstrates potential for replication in both public and private hospitals and contributes to the advancement of Lean health care in Brazil.